PENGARUH KONTEN LGBT PADA MEDIA SOSIAL TERHADAP PERILAKU CYBER BULLYING PADA KALANGAN REMAJA - Anya Naryakusuma; Vincentius Antoni Wijaya (Communications, 2021)
ABSTRACT Social media is currently becoming an addiction for all circles of society. Starting from small children to adults, on average, they have a cellphone or gadget to play social media. Many social media platforms are used by the public. One example is TikTok. By using Tiktok, users can easily get video shows with various kinds of content. Starting from business info, health, or just entertainment. But as time goes by, the content on social media is getting less and less regulated. Things that shouldn't be displayed because of things like unpleasant or 18 years and above are getting easier to enter users' social media. One of the contents that do not deserve to be displayed on social media is content that smells of Pelangi or LGBT people. This study uses quantitative methods, researchers distribute questionnaires to a population sample of 100 respondents. The paradigm of this research is the positivist paradigm because the researcher wants to test and find out whether there is an influence of LGBT content on social media on cyberbullying behavior among teenagers. The results show that the second variable has a strong and positive influence, which means that LGBT content on social media can increase cyberbullying behavior among teenagers. Keywords: Social Media, Cyberbullying, Pengaruh Konten